Is a different perspective helpful? Assessing the validity of peer ratings of goal orientation. - Espejo, Jazmine. (My University, 2006)
The present study was the first to examine the validity of peer ratings of goal orientation. I examined peer-assessed goal orientation in a collaborative training environment with a complex task. The reliability and structural, convergent, discriminant, and predictive validity of peer ratings were examined. Regarding predictive validity, I examined the incremental contribution of peer ratings above and beyond self ratings in the prediction of skill acquisition and post-training self-efficacy. The results showed that (1) self and peer ratings have similarly high levels of internal consistency, (2) there is little agreement and convergence between self and peer ratings, (3) self and peer ratings have similar structures, and (4) peer ratings provide incremental validity beyond both self ratings and prior performance in predicting future skill acquisition and post-training self-efficacy.
Keywords: Goal (Psychology); Peer review in psychology.; Psychology, Industrial.